2019
DOI: 10.3390/foods8090370
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Nutrition Review of Grain-Based Muesli Bars in Australia: An Audit of Supermarket Products

Abstract: Muesli bars are consumed by 16% of children, and 7.5% of adults, and are classified as discretionary in Australian Dietary Guidelines, containing “higher fat and added sugars” compared with core food choices. This study aimed to provide a nutritional overview of grain-based muesli bars, comparing data from 2019 with 2015. An audit of muesli bars, grain-based bars, and oat slices was undertaken in January 2019 (excluding fruit, nut, nutritional supplement, and breakfast bars) from the four major supermarkets in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…A recognised process was used to conduct an audit of plant-based meat substitutes [29,30] in the four major supermarkets (Aldi, Coles, IGA, and Woolworths) of metropolitan Sydney in June 2019, replicating a process that was conducted on the same category in 2015. These supermarket chains represent more than 80% of total Australian market share [31], and were chosen in an effort to reflect choices available to the majority of Australian shoppers.…”
Section: Methodsmentioning
confidence: 99%
“…A recognised process was used to conduct an audit of plant-based meat substitutes [29,30] in the four major supermarkets (Aldi, Coles, IGA, and Woolworths) of metropolitan Sydney in June 2019, replicating a process that was conducted on the same category in 2015. These supermarket chains represent more than 80% of total Australian market share [31], and were chosen in an effort to reflect choices available to the majority of Australian shoppers.…”
Section: Methodsmentioning
confidence: 99%
“…A cross-sectional survey of plant-based milk alternatives was conducted between November 2019 and January 2020 in Metropolitan areas of Melbourne and Sydney. The data collection process replicated a previously recognised procedure [10,52]; however, the examination included three market categories: retail supermarkets, health food stores and local independent cafes with non-dairy milk offerings. The following major supermarkets were surveyed: Woolworths Group, Coles, Aldi and Independent Grocers of Australia (IGA), which collectively constitute 80.1% of the Australian grocery market share [53].…”
Section: Methodsmentioning
confidence: 99%
“…The system ranks packaged foods on a scale between 0.5 (1/2) to 5 stars, with more stars indicating a healthier product, and scores foods based on their 'negative nutrients' (kilojoules, sodium, saturated fat, and total sugars), and 'positive' points, including fruit, vegetables, nuts, or legumes, as well as dietary fibre and protein [47]. The HSR does not directly reward grain foods for containing whole grain, and research has shown this translates to only minor score differences between refined and whole grain foods, such as white and brown rice, or pasta [48], but also snacks, such as muesli bars [34], failing to adequately communicate whole grain's health benefits. This omission has been justified by the fact that some whole grain foods may achieve a higher score based on their dietary fibre content; however, fibre is known as a poor indicator of whole grain.…”
Section: Discussionmentioning
confidence: 99%
“…An audit is defined as a 'systematic review or assessment of something' [30]. This recognised process has been published previously [31][32][33][34], and was conducted in the four major supermarket chains (Aldi, Coles, Woolworths, IGA) in metropolitan Sydney, in order to capture the breadth of products available in Australia. Smartphones were used to record all on-pack information, including ingredients, nutrition information, nutrition and health claims, and any logos or endorsements, including the Health Star Rating.…”
Section: Methodsmentioning
confidence: 99%